Seismic images of crust and upper mantle in Central Iran (from Jiroft to Ashtian) via teleseismic waves - JAVADI, Shahireh; TAGHIZADEH-FARAHMAND, Fataneh; GHEITANCHI, Mohammad Reza (Contributions to Geophysics and Geodesy, 2020)
A detailed knowledge of the thickness of crust and upper mantle structure is important for understanding a plate tectonics and geodynamics in the region. We use body wave for detecting details of the subsurface structure. The information in this research is collected from a seismic linear profile that extends across the Sanandaj-Sirjan metamorphic zone in seismic states of Central Iran and Zagros. We compute P receiver functions to investigate crustal and upper mantle discontinuities. We use teleseismic events (mb ≥ 5.5, 30° < Δ < 95°) registered between 1996 and 2018 and recorded at 10 short-period stations with 3 components and 17 broadband stations with high signal to noise ratio. The observed depth of Moho in the study area is approximately 50 km and rises to 70 km at the end of the seismic linear profile beneath Sanandaj-Sirjan zone. In Central Iran, depths discontinuities in the transition zone are shown by the reference model of deviation, which can be attributed to the convergence of Arabian plate with the Central Iran plateau. Also, the study area was identified as geothermal susceptibility by SUNA and this observation was confirmed.